The Working Alliance in Teaching and Learning: Theoretical Clarity and Research Implications - Daniel Rogers (International Journal for the Scholarship of Teaching and Learning, 2009)
The working alliance has proven to be a valuable concept in psychotherapy research, but its utility in understanding change processes in teaching and learning has yet to be realized. Despite previous applications of the concept to educational contexts, empirical research on the working alliance in student-teacher collaborations is lacking. To address this disconnect and encourage research, I present an overview of working alliance theory, clarify the application of the concept to educational contexts, and explore its relationship to the scholarship of teaching and learning. Potential applications of working alliance theory to teaching and learning research are considered as informed by developments within psychotherapy research.